Gen-Z Perception towards Employee Satisfaction Amidst Digitalization Era in Jakarta, Indonesia - Theofilus Calvin P. Santosa; Ronan W. Adrianto; Frida A. Ramadhanty; Rizki P. Pambudhi (CV. Ulil Albab Corp, 2025)
Purpose: The purpose of this study is to examine how Gen-Z employees perceive the impact of workplace digitalization on their communication, collaboration, productivity, and overall employee satisfaction. Design/Methodology/Approach: A qualitative research approach was employed, involving semi-structured interviews with 16 Generation Z employees in Jakarta from diverse sectors. Data were analyzed using a coding framework to identify themes related to digitalization and employee satisfaction. Findings: The findings highlight the dual-edged nature of digitalization, emphasizing the need for organizations to thoughtfully integrate digital solutions that align with the unique preferences and expectations of Generation Z. Practical Implications: This research offers practical insights for businesses seeking to engage this generation, showcasing the importance of balancing technological advancements with human- centric workplace policies to sustain satisfaction and productivity in the digital era. Originality/Value: The study offers a fresh perspective on how digitalization influences employee satisfaction among Generation Z in Jakarta, highlighting its dual impact through a qualitative lens.